2014
DOI: 10.1016/j.ctim.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The association between blood lipid and phlegm turbidity syndrome of angina pectoris: A systematic review and meta-analysis

Abstract: When comparing with Traditional Chinese Medicine (TCM) syndromes of asthenia nature, such as YDS, QYDS, and heart qi deficiency syndrome), the levels of TG, TC, and LDL-C were higher in phlegm turbidity syndrome. However, for sthenia syndromes such as Qi stagnation syndrome (QSS), heart blood stasis syndrome (HBSS), and CCS, there was no obvious difference. Furthermore, HDL-C levels in the phlegm turbidity group were lower than those of the non-phlegm group. Nevertheless, these results should be confirmed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The type of Qi stagnation and blood stasis selected for this study is one of the main types of thoracic obstruction. In ancient TCM, the heart is the master of the blood vessels and runs Qi and blood in the meridians to moisten the body; if the heart Qi sinks, it is difficult to move Qi and blood, fluid stagnation, Qi blockage, blood flow is not smooth accumulation of stasis, retention in the meridians, paralysis blocking chest yang, and inaccessibility of the heart chakra develops into thoracic obstruction [ 14 16 ]. The occurrence of Qi stagnation and blood stasis type of thoracic obstruction begins with the sinking of heart Qi.…”
Section: Discussionmentioning
confidence: 99%
“…The type of Qi stagnation and blood stasis selected for this study is one of the main types of thoracic obstruction. In ancient TCM, the heart is the master of the blood vessels and runs Qi and blood in the meridians to moisten the body; if the heart Qi sinks, it is difficult to move Qi and blood, fluid stagnation, Qi blockage, blood flow is not smooth accumulation of stasis, retention in the meridians, paralysis blocking chest yang, and inaccessibility of the heart chakra develops into thoracic obstruction [ 14 16 ]. The occurrence of Qi stagnation and blood stasis type of thoracic obstruction begins with the sinking of heart Qi.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic factors may disrupt the function of lungs, block Qi, and blood circulation, influence the function of organs, and cause numerous negative changes in the body. Thus, phlegm is the pathological product of the disturbance of body fluid in the transportation and stagnation of body fluids [23]. Moreover, phlegm syndrome is almost always accompanied by other syndromes, such as phlegm-damp, phlegm-heat and phlegm-stasis syndromes [12, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-circulation obstruction, abnormal haemorheology, unstable haemodynamics, abnormal platelet and endothelium, dysfunctional anticoagulation, and fibrinolysis: all conditions which lead to blood stasis [38]. Some studies proposed that possessing Stasis BC is significantly associated with hyperlipidaemia, atherosclerosis, coronary heart disease, or coronary artery disease [38][39][40]. Several studies demonstrated that olanzapine is a relatively unsafe drug, especially for patients who have coronary heart disease [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%